Laminar film condensation inside and outside vertical diverging/converging small channels : a theoretical study - Liu, Pengfei (2021)
A theoretical study is conducted on laminar film condensation inside and outside the diverging/converging channels. An exact solution together with two approximate solutions are developed and compared. The rate of increment of the dimensionless film thickness is found to increase as the diverging angle increases near the inlet condensing region. A flooding effect exists due to the constricting channel diameter for condensation on converging channels. This leads to the rate of increment of the dimensionless film thickness to increase significantly near the outlet condensing region. However, the curvature effect dominates the flooding effect such that the local heat transfer coefficient increases near the outlet condensing region. A bending effect exists in the diverging/converging channels such that the linear relationship of log (hx) and log (x) fails to hold. The condensation heat transfer coefficient decreases with the increase in the diverging angle. The condensation heat transfer coefficient on both inside and outside channels can be substantially enhanced by using the converging channels. However, it deteriorates significantly when diverging channels are utilized. The surface tension and the liquid subcooling effects are also investigated. It is found that the effect of liquid subcooling is generally insignificant on condensation heat transfer. The effect of surface tension is also small in most of the cases. However, when the diverging angle approaches the critical angle, its influence becomes significant.